(3efgGL GdcJGHs - (3GdeXaQ Hf eMeO Hf GdeXaQ Hf GdMSjf GdefHLjs
(3ChdgG (B:s
(3hHYO aEfi cJGHi gPG de GTQYJ ajg PGgHkG TQYJ efg GdHGH GdChd ai PcQ Gddg YR hLd s
(3BNQgG (B:s
(3hHPcQfi TLhRfi SGHb GdWYf eG LOkG jHcjfi GdMeGe EPG Zfi Je GdcJGH s
(3gPG GdcJGH gh eShOI GdeDdas
(3jMJhi Ydi (B51 (3HGHs
(3JQbje UaGJge eJSdSd s
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3eJaQbGJs